Temporin A and Bombinin H2 Antimicrobial Peptides Exhibit Selective Cytotoxicity to Lung Cancer Cells - Lucy Swithenbank; Phillipa Cox; Llinos G. Harris; Edward Dudley; Kathryn Sinclair; Paul Lewis; Floriana Cappiello; Claire Morgan (Scientifica)
Background. Recently, antimicrobial peptides (AMPs) have been investigated for their use in cancer therapy. They have been reported to selectively target and kill cancer cells whilst leaving normal healthy cells unaffected. Certain Anura AMPs have expressed selective cytotoxicity against tumour cells. Aim. To test the potential of Anura AMPs bombinin H2, bombinin H4, temporin A, and temporin L for use as therapeutic agents for non-small cell lung carcinoma (NSCLC). Methods. Cytotoxic effects on NSCLC cell lines A549 and Calu-3 and normal epithelial cell line Beas-2B were tested using the CellTox Green Cytotoxicity Assay. Their haemolytic effects on human erythrocytes were also tested for their clinical relevance. Cell membrane profiling, using MALDI-TOF, was performed to ascertain if membrane characteristics of the NSCLC and Beas-2B cell lines may contribute to the AMPs mode of action. Results. Bombinin H4 (100–1.5 μM, p<0.05) and temporin A (100–50 μM, p<0.05) showed selective cytotoxicity towards the NSCLC cell lines. Furthermore, they exhibited low levels of haemolytic activity (bombinin H4, 0.061%; temporin A, 0.874%) comparable to untreated cells. Cell membrane profiling showed the phospholipid composition of normal epithelial cell line Beas-2B to be divergent from the cancerous cell lines. However, there was an overlap in the phospholipid profiles of the NSCLC cell lines supporting the hypothesis that the AMPs may have a selective affinity via the membrane composition of cancerous cell lines. Conclusion. These results suggest that bombinin H4 and temporin A show potential for application in lung cancer therapies. Further in vitro and in vivo studies are required to develop a greater understanding of their use as anticancer agents.